Attempts to protect goats against challenge with Trypanosoma vivax by initiation of primary infections with large numbers of metacyclic trypanosomes - Vos, G.J.; Moloo, S.K.; Nelson, R.T.; Gardiner, Peter R. (Cambridge University Press, 1988)
Attempts were made to immunize goats by infection with large numbers of metacyclic trypanosomes of a clone ofTrypanosoma vivax, followed by chemotherapy. Five groups of 6 goats each were infected intradermally with 5 different doses of cultured metacyclics ofT. vivax, ranging from 102to 106trypanosomes/goat. Four weeks after infection, the goats were treated with 10 mg/kg diminazene aceturate (Berenil, Hoechst A.G.). Three weeks after treatment, 3 goats in each group were challenged intradermally with 104homologous metacyclics derived from culture. The remaining 3 goats in each group were challenged by 20 tsetse infected with the homologous clone. Five out of 30 goats were resistant to homologous challenge; 4 of the goats that had been challenged with cultured parasites, and 1 that had been challenged by tsetse. In each group 1 goat was protected. Protection was therefore not apparently influenced by the number of trypanosomes used to establish the primary infection. In another experiment, 6 goats were each infected by feeding 100 tsetse on the goats for 15 consecutive days. Three weeks after infection the goats were treated with Berenil and 3 weeks later challenged by 20 tsetse infected with the homologous clone. Three out of the 6 goats resisted challenge. The susceptible goats in both experiments, however, showed a reduction in the peak of parasitaemia following challenge compared with both challenge controls and the initial infections. Lytic antibodies to cultured metacyclics ofT. vivaxwere detected in goats that resisted challenge after a primary infection with cultured metacyclics, and in resistant and susceptible goats after a primary infection by tsetse. All infected goats produced lytic antibodies to live bloodstream forms, as well as antibodies to bloodstream form lysates (demonstrated by ELISA). It is suggested that the immunity that had been induced in some of the experimental animals is due to antibody responses to both metacyclic and bloodstream variable antigen types (VATs) expressed during infection.